Effect of Social Distancing on COVID-19 Incidence and Mortality in Iran Since February 20 to May 13, 2020: An Interrupted Time Series Analysis - Alimohamadi, Yousef (Risk Manag Healthc Policy, 2020)
BACKGROUND AND OBJECTIVE: Numerous actions have been taken to control the COVID-19 pandemic and reduce their morbidity and mortality. One of the most important measures in this regard is social distancing. However, there is limited evidence on the effectiveness of social distancing on COVID-19 incidence and mortality. Thus, the current study aimed to assess the effectiveness of social distancing measures on the COVID-19 incidence and mortality in Iran. MATERIALS AND METHODS: In the current quasi-experimental study, we evaluated the daily incidence cases and the number of deaths of COVID-19 in Iran before and after the implementation of social distancing measures. The segmented regression model was used to analyze the data. We also performed the interrupted time series (ITS) analysis using Newey ordinary least squares (OLS) regression-based methods. RESULTS: After the implementation of social distancing, the trend of both daily new cases and deaths due to COVID-19 was decreasing [(ß = −1.70 (95% CI = [−2.30 – −1.10; P < 0.001])) and (ß = −0.07 (95% CI = [−0.10 − −0.05; P < 0.001], respectively))]. CONCLUSION: Social distancing along with other public health interventions could reduce the morbidity and mortality of COVID-19 to some degrees, and it seems to be crucial to control the pandemic.